Chemometric assisted green extraction of tyrosinase inhibitor from Durio zibethinus rind for skin whitening agents in cosmetic products - Sofiyyah, Ismail; Erna Normaya, .; Syamimi Sulfiza, Shamsuri; Anwar, Iqbal; Mohd Bijarimi, Mat Piah; Sharifuddin, Md Zain; Mohammad Norazmi, Ahmad (Elsevier, 2024)
Cosmetics typically contain artificial substances that could be harmful to people's health. Extended usage and exposure to these harmful substances are frequently linked to a number of negative impacts and illnesses. This study processed a Durio zibethinus rind, rich in natural antityrosinase properties, with a chemometric-assisted green extraction system. The TPC value was obtained at the optimum conditions (34.4 MPa, 62°C, and 86 min). GC-MS and FTIR spectroscopy were performed to identify the phenolic compounds and their functional group, respectively. The optimized extract contains 77 % of the mushroom tyrosinase activity. PCA shows that aspidospermidin-17-ol,1-acetyl-19,21-apoxy-15,16-dimethoxy- (AP) resembles the similar cluster with hydroquinone. COSMO-RS was used to investigate the extraction mechanism of CO2 and AP during the SFE process. DFT and molecular docking were used to calculate the chemical reactivity and explain the tyrosinase inhibition mechanism, respectively. ADME-Tox and OSIRIS Property Explorer showed no violation of Lipinski’s rule, and toxicity with AP. In conclusion, a high-value, natural and safe cosmetic ingredient (AP) for cosmetopea was discovered using an innovative green extraction system.